Runaway electron mitigation by 3D fields in the ASDEX-Upgrade experiment. (10th November 2017) - Gobbin, M; Li, L; Liu, Y Q; Marrelli, L; Nocente, M; Papp, G; Pautasso, G; Piovesan, P; Valisa, M; Carnevale, D; Esposito, B; Giacomelli, L; et al.
Abstract: Disruption-generated runaway electron (RE) beams represent a severe threat for tokamak plasma-facing components in high current devices like ITER, thus motivating the search of mitigation techniques. The application of 3D fields might aid this purpose and recently was investigated also in the ASDEX Upgrade experiment by using the internal active saddle coils (termed B -coils). Resonant magnetic perturbations (RMPs) with dominant toroidal mode number n  = 1 have been applied by the B -coils, in a RE specific scenario, before and during disruptions, which are deliberately created via massive gas injection. The application of RMPs affects the electron temperature profile and seemingly changes the dynamics of the disruption; this results in a significantly reduced current and lifetime of the generated RE beam. A similar effect is observed also in the hard-x-ray (HXR) spectrum, associated to RE emission, characterized by a partial decrease of the energy content below 1 MeV when RMPs are applied. The strength of the observed effects strongly depends on the upper-to-lower B -coil phasing, i.e. on the poloidal spectrum of the applied RMPs, which has been reconstructed including the plasma response by the code MARS-F. A crude vacuum approximation fails in the interpretation of the experimental findings: despite the relatively low β ( < 0.5 % ) of these discharges, a modest amplification (factor of 2 ) of the edge kink response occurs, which has to be considered to explain the observed suppression effects.